Functional Amnesia: Clinical Description and Neuropsychological Profile of 10 Cases - Kritchevsky, Mark (Cold Spring Harbor Laboratory Press, 2004)
We carried out the first neuropsychological study of a series of patients with functional amnesia. We evaluated 10 patients, first with a neurological examination and then with three tests of anterograde amnesia and four tests of retrograde amnesia. Excluding one patient who later admitted to malingering, all patients had a significant premorbid psychiatric history and one or more possible precipitating factors for their amnesia. Eight of the 10 patients still had persistent retrograde amnesia at our last contact with them (median = 14 mo after the onset of amnesia). On tests of anterograde amnesia, the patients performed normally as a group, though some patients scored poorly on tests of verbal memory. On tests of retrograde amnesia, all patients had difficulty recollecting well-formed autobiographical memories of specific events from their past. In contrast, patients performed as well as controls at distinguishing the names of cities from fictitious city names. On remote memory tests for past public events and famous faces, different patients exhibited different but internally consistent patterns of impaired and spared performance. The variability in the clinical and neuropsychological findings among our patients may be understood by supposing that memory performance is poor in proportion to how directly a test appears to assess a patient's commonsense concept of memory. The presentation of patients with functional amnesia is as variable as humankind's concept of what memory is and how it works.